Brexit and Its Implications for the UK and Europe - Çınar, Özgür H. (Border Crossing, 2025)
Brexit has been recorded as one of the biggest political and economic ruptures in modern European history. On 23 June 2016, 51.89% of the public voted to leave the European Union (EU) in a referendum. This decision had profound implications not only for the United Kingdom (UK), but also for the European and world economy. Therefore, in April 2025, we addressed the impact of Brexit on Europe and the UK in a conference at the University of Greenwich. This special issue includes papers by scholars who presented their paper at the conference, as well as by authors who were unable to attend but are now contributing to this special issue.